ANALYSIS INFLUENCE OF PERSONAL SELLING, SERVICE QUALITY & PRODUCT MIX ON CUSTOMER LOYALTY AT DIAH GROCERY STORE DURING POST PANDEMIC - Wijaya, Natalia (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine the effect of Personal Selling, Service Quality and Product Mix on Customer Loyalty at Diah Grocery Store. The research method used is quantitative research with a survey method that uses a questionnaire as a research instrument to collect data. The population in this study were all buyers who had shopped at the Diah Grocery Store with an uncertain amount. By using hair formula, the number of indicator multiplied by 10 to obtain 160 respondents. Multiple linear regression research test is used as an analytical tool to determine how the influence between independent and dependent variables. The results of this study indicate that either partially or simultaneously the variables of Personal Selling, Service Quality and Product Mix have a significant effect on Customer Loyalty at Diah Grocery Store. The variables of Personal Selling, Service Quality and Product Mix variables are able to explain the variation that occurs in Diah Grocery Store Customer Loyalty by 51.1%.